1999
DOI: 10.1111/j.1447-0756.1999.tb01176.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methamphetamine on Male Mice Fertility

Abstract: The effect of methamphetamine (MAMP) on the ability of males to mate with females and to impregnate them was examined in 8-week-old ICR mice. Male mice that had been administered an intraperitoneal injection of MAMP (15 mg/kg, 7.5 mg/kg, or 3.75 mg/kg) or saline were housed with females 24 or 48 hours later. The vaginal plugs were checked, and the number of births was counted. The effect of MAMP on sperm motility and the serum testosterone (TS) concentration was also examined. Methamphetamine was observed to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…It is shown that there is a positive relationship between sperm chromatin defects and cell death or apoptosis (38). Similar to our study, Yamamoto and colleagues reported that administration of MA reduces the spermatogenesis and increases apoptosis in spermatogonial cell line in rat (36). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is shown that there is a positive relationship between sperm chromatin defects and cell death or apoptosis (38). Similar to our study, Yamamoto and colleagues reported that administration of MA reduces the spermatogenesis and increases apoptosis in spermatogonial cell line in rat (36). …”
Section: Discussionsupporting
confidence: 91%
“…Our findings were similar to the study by Alavi and colleagues which have demonstrated that frequent consumption of high dosage of MA may reduce the number of sperm in the epididymis tail and has negative effects on reproductive system in male rats (34). Additionally, several experimental studies showed that administration of different dose of MA caused decreasing in the sperm count and normal morphology (35, 36). …”
Section: Discussionmentioning
confidence: 99%
“…METH causes sexual dysfunction in mammals, inhibiting sperm motility [29], and amphetamines, which are structurally similar to METH, retard ejaculation in humans [30]. Although METH is known to have negative effects on male fertility [29] little is known regarding the molecular impacts of METH on spermatogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Although METH is known to have negative effects on male fertility [29] little is known regarding the molecular impacts of METH on spermatogenesis. In our study, we detected seven METH-responsive genes and proteins that are associated with reproductive functions in males (Tables S2 & S3), some of which are evolutionarily conserved in humans.…”
Section: Resultsmentioning
confidence: 99%
“…Yamamoto et al ( 1999 ) , funding not indicated, examined the effects of methamphetamine exposure on reproductive toxicity in male mice. Eight‐week‐old male ICR mice were given a single i.p.…”
Section: 0 Reproductive Toxicity Datamentioning
confidence: 99%